2019
DOI: 10.3348/kjr.2018.0611
|View full text |Cite
|
Sign up to set email alerts
|

Response Assessment with MRI after Chemoradiotherapy in Rectal Cancer: Current Evidences

Abstract: Baseline magnetic resonance imaging (MRI) has become the primary staging modality for surgical plans and stratification of patient populations for more efficient neoadjuvant treatment. Patients who exhibit a complete response to chemoradiotherapy (CRT) may achieve excellent local tumor control and better quality of life with organ-preserving treatments such as local excision or even watch-and-wait management. Therefore, the evaluation of tumor response is a key factor for determining the appropriate treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 73 publications
1
33
0
1
Order By: Relevance
“…However, several recent studies have reported that the oncologic outcomes are better correlated with pathological evaluation of the neoadjuvant CRT response ( 3 4 5 ). Qualitative evaluation using tumor regression grade (TRG) to evaluate tumor cell replaced by fibrosis in response to CRT was suggested as a good parameter, and it has been widely accepted as a practical parameter for oncologic prognosis in rectal cancer patients ( 6 7 8 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, several recent studies have reported that the oncologic outcomes are better correlated with pathological evaluation of the neoadjuvant CRT response ( 3 4 5 ). Qualitative evaluation using tumor regression grade (TRG) to evaluate tumor cell replaced by fibrosis in response to CRT was suggested as a good parameter, and it has been widely accepted as a practical parameter for oncologic prognosis in rectal cancer patients ( 6 7 8 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most popular suite of radiomic features involve extracting texture responses, which could help quantify the imaging appearance of deep stromal alterations caused by fibrosis [23] appearing within the rectal wall after nCRT. Other hallmarks of nCRT impact in the rectum include changes in rectal wall thickness due to the development of tumor necrosis or inflammation [24].…”
Section: Introductionmentioning
confidence: 99%
“…After nCRT, most LARCs demonstrate variable degrees of tumor response, including pathologic complete remission, in 4%–31% of patients. Patients with complete remission by nCRT can achieve excellent local tumor control and a better quality of life with organ-preserving treatments such as local excision or even watch-and-wait management ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, surgeons are often reluctant to perform sphincter preservation given insufficient reliability for differentiating between residual tumors and nCRT-related changes, such as edema, necrosis, and fibrotic changes. Therefore, radiologists should be aware that their interpretation might result in a faulty decision when selecting an organ-preserving treatment or performing unnecessary radical surgery, which compromises the quality of life of patients ( 3 ).…”
Section: Introductionmentioning
confidence: 99%